Development of new fabrication and measurement techniques of micro-electrodes with high aspect ratio for micro EDM using typical EDM machine - Hourmand, M. (Elsevier B.V., 2017)
Micro-electrodes are used for micro holes EDM drilling in miniaturized products. This study represents novel fabricating and measuring processes of high aspect ratio micro-electrodes based on horizontal moving block electrical discharge grinding (horizontal moving BEDG [HM-BEDG]) and gage block with a typical EDM machine, as well as solving the problems that occur during micro-electrode fabrication. The EDM machine has been used as a coordinate measuring machine (CMM) for measuring micro-electrode diameter, where the gage block acts as a probe and the micro-electrode as a workpiece. As a result, a micro-electrode with the highest aspect ratio (over 60.25) was fabricated successfully with 78.19 μm diameter and 4.70 mm length after producing a through micro hole with 134.5 μm diameter on WC[sbnd]Co. As these processes are simple and do not require high investment for special equipment, micro-electrodes can be fabricated and measured for micro EDM drilling and milling in conventional workshops equipped with EDM machines.